Analisis Framing Pemberitaan Efisiensi Anggaran oleh Pemerintah Indonesia pada Media Online detik.com dan tempo.co - Banyu Biru; Hamidah Hamidah; Muslimin Muslimin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The Indonesian government's 2025 budget efficiency policy has sparked controversy among the public, particularly regarding its impact on public sectors such as education and development. These differing views are also reflected in online media reports, which tend to have different perspectives and angles. This study focuses on how online media constructs the reality of budget efficiency policies and the differences in framing used by detik.com and tempo.co in reporting on this issue. This study aims to determine the framing of the Indonesian government's budget efficiency policies by detik.com and tempo.co and to compare how the two media outlets frame these policies. The research method used is a descriptive qualitative approach with Zhongdang Pan and Gerald M. Kosicki's framing analysis model, which includes syntactic, script, thematic, and rhetorical structures. The research data consists of budget efficiency news articles published in February 2025 in both media outlets. The results of the study show that detik.com tends to frame the budget efficiency policy positively by positioning the government as a decisive and pro-people reform actor, while tempo.co presents a critical framing by highlighting policy inconsistencies, social impacts, and the potential for a fiscal governance crisis. This study confirms that differences in framing are influenced by the agenda setting of each media outlet, resulting in different constructions of reality in interpreting the government's budget efficiency policy.